Ionic liquids or eutectic solvents? Identifying the best solvents for the extraction of astaxanthin and β-carotene from Phaffia rhodozyma yeast and preparation of biodegradable films - Mussagy, Cassamo U. [UNESP]; Santos-Ebinuma, Valéria C. [UNESP]; Herculano, Rondinelli D. [UNESP]; Coutinho, João A. P.; Pereira, Jorge F. B.; Pessoa, Adalberto (Royal Society of Chemistry (RSC), 2022)
In order to replace conventional organic solvents with more benign equivalents such as ionic liquids or eutectic solvents, in this work we attempt to develop a simple and ecofriendly process using these alternative solvents for the extraction of astaxanthin and β-carotene from Phaffia rhodozyma biomass, which could simultaneously be used as a colorant and plasticizer agent for the preparation of bioactive starch-based biodegradable films without further purification. The use of cholinium-based eutectic solvents appears to be a promising solution envisioning the development of functionalized carotenoid-rich biofilms.